2019
DOI: 10.18609/cgti.2019.175
|View full text |Cite
|
Sign up to set email alerts
|

Cost modelling comparison of adherent multi-trays with suspension and fixed-bed bioreactors for the manufacturing of gene therapy products

Abstract: There is huge pressure on biomanufacturing facilities due to high demand for gene therapy products such as recombinant adeno-associated viral (AAV) vectors made under current good manufacturing practice (GMP) conditions. The constraints of the scale-up process are rarely taken into consideration during clinical process development, with many facilities simply scaling-out adherent cell stack protocols, procedures, and test methods. In order to demonstrate the importance of cost economics linked to the choice of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 3 publications
1
11
0
Order By: Relevance
“…A recent study evaluating different production platforms for adeno‐associated virus estimated DSP costs to be equal to about 40% of the overall cost of good per dose for a 1000 L suspension cell culture in batch. [ 55 ] However, in this case, neither the DSP technique and DSP yield nor DSP costs per dose were influenced by the intensification of the USP. Thus, the overall impact of DSP on the economical modelling was considered to be negligible.…”
Section: Discussionmentioning
confidence: 91%
“…A recent study evaluating different production platforms for adeno‐associated virus estimated DSP costs to be equal to about 40% of the overall cost of good per dose for a 1000 L suspension cell culture in batch. [ 55 ] However, in this case, neither the DSP technique and DSP yield nor DSP costs per dose were influenced by the intensification of the USP. Thus, the overall impact of DSP on the economical modelling was considered to be negligible.…”
Section: Discussionmentioning
confidence: 91%
“…Intensification can be achieved with bioreactors coupled to devices for harvesting of infectious units with subsequent continuous purification. A techno‐economic analysis could provide insights about cost differences between a batch and a perfusion process for viral vector production (Cameau et al, 2019; Gränicher et al, 2020; Pearson, 2020), similarly to recombinant protein production (Klutz et al, 2016; Lim et al, 2006; Pleitt et al, 2019; Pollock et al, 2013). This could allow identifying key factors and bottlenecks allowing cost‐savings.…”
Section: Introductionmentioning
confidence: 99%
“…systems [2]. The study also showed that in some conditions, there are potential cost benefits to adherent methods.…”
mentioning
confidence: 76%